The Development of Carrom Learning Media to Improve the Ability of Mild Mentally Retarded Children to Read Words in SLB Negeri 1 Makassar - Hasriani Hasriani; Syamsuddin Syamsuddin; Abd. Hadis; Usman Usman (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2022)
This study aims to produce carrom media to improve the ability to read words of mild mentally retarded children. The study implemented the research and development design based on the research stages of Borg & Gall. Data collection techniques used in this study were interviews, observations, and questionnaires. The data were analyzed through qualitative and quantitative analysis techniques. The object of this research is the modified Carrom learning media, with the research stages covering; 1) the information gathering stage; 2) the planning stage; 3) the product development stage, and 4) the design validation and revision stages. The results of this study are; needs analysis of grade 3 mentally retarded students at SLB Negeri 1 Makassar showed that teachers and students needed modified carrom as learning media, carrom media design/prototypes were modified starting fromplanning, product development, expert validation, and validity testing stages and the validation from the material experts showed that the media was considered valid and the validity level was in the very good category so that the modified carrom media deserved to be tested and resulted in a very good category.